Commodity Taxation and Regulatory Competition - Simone Moriconi; Pierre M. Picard; Skerdilajda Zanaj (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper studies theoretically and empirically competition in commodity taxation and product market regulation between trading partner countries. We present a two-country general equilibrium model in which destination-based commodity taxes finance public goods, and product market regulation affects both the number of firms in the market and product diversity. We provide empirical evidence based on data for 21 OECD countries over the 1990-2008 period. Our results suggest that commodity taxation and product market regulation are interdependent policies. We find absence of strategic interaction in commodity taxation between governments. Furthermore, we show that domestic regulation has a negative effect on domestic commodity taxation. Finally, we demonstrate that product market regulation is a strategic complementary policy.
Keywords: F00; H10; H70; H87; L50; 330; regulation; commodity tax; strategic interactions